1985
DOI: 10.2503/jjshs.53.383
|View full text |Cite
|
Sign up to set email alerts
|

The Relation Between Growth Inhibitor and Phenols in Developing Berry of ^|^lsquo;Muscat of Alexandria^|^rsquo; Grape

Abstract: Although the total phenol content in the berry of grape (Vitis vinifera L. cv. `Muscat of Alexandria') was kept constant during period II and III , the qualitative changes of the phenols could be found before and after veraison. Three of 7 fractions, which were separated from the berry by several organic solvents, exhibited growth inhibitory activity in the avena coleoptile straight growth test. By the 1-demensional paper chromatogram, the activity was found at the Rf differing from that of ABA in period II, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1987
1987
2003
2003

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…In our study, however, no peak of ABA was found at that time. The decline in ABA concentration found in both the fl esh and the seed was similar to observations by Ohkawa (1985) and Panday and Singh (1989). These results suggest that ABA may not be re spon si ble for the slow berry growth during Stage II.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In our study, however, no peak of ABA was found at that time. The decline in ABA concentration found in both the fl esh and the seed was similar to observations by Ohkawa (1985) and Panday and Singh (1989). These results suggest that ABA may not be re spon si ble for the slow berry growth during Stage II.…”
Section: Discussionsupporting
confidence: 90%
“…On the contrary, low levels of ABA might be closely related to the rapid growth and development of the seeds. Low concentrations of ABA in the fl esh suggest that there might be other growth inhibitors such as phenolic compounds, which decrease the growth of the fl esh (Ohkawa, 1985).…”
Section: Discussionmentioning
confidence: 99%